The Principle of Integrated Islamic Education - Imam Bahroni (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2014)
The development of integrated Islamic education has introduced a new trend in formal educational institutions in Indonesia. The pondok constitutes a typical Islamic boarding school often run and owned by individual religious teachers (kyai), wherein the Islamic subjects become the priority. The references of these Islamic subjects derived from Islamic classical books (kitab kuning) as the aim of this pondok education system is to produce religious scholars. Slightly different from pondok is the madrasah. This educational institution generally teaches 30 percent Islamic subjects alongside secular subjects. Over the last 20 years, many pondoks have adopted the madrasah system and included instruction in secular subjects in their curriculum. This article aims at elaborating the foundation of integrated Islamic education from the conception of Muslim scholars whose original views derived from the Holy Qur’an and the Prophetic Tradition.